A New Multiplex Genetic Detection Assay Method for the Rapid Semi-Quantitative Detection of Six Common Curable Sexually Transmitted Pathogens From the Genital Tract - Sun, Zhaoyang; Meng, Jun; Wang, Su; Yang, Feng; liu, Tao; Zeng, Xianping; Zhang, Dijun; Zhu, Haowei; Chi, Wenjing; Liu, Yixin; Jiang, Wenrong; Ding, Li; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Sexually transmitted infections (STIs) are some of the most common communicable conditions and exert impact on the health and lives of many hundreds of millions of people across the world every year. Screening high-risk populations and conducting comprehensive detection tests would lead to a significant improvement in preventing the transmission of STIs and help us to provide rapid treatment to those affected. Here, we successfully established and validated a novel high-throughput multiplex gene detection system (HMGS) for the simultaneous and semiquantitative detection of six important curable sexually transmitted pathogens in a single reaction from secretions samples. Method: Fluorescently labeled primers were designed to target specific conserved and single-copy gene fragments of Ureaplasma urealyticum, Mycoplasma hominis, Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, and Treponema pallidum . The specificity and sensitivity of the STI-HMGS was validated and optimized using plasmids and quantitative genomic DNA. Next, we validated the performances of the STI-HMGS for clinical application by testing samples of clinical secretions collected from patients. Results derived from the STI-HMGS were then compared with three approved commercialized kits, followed by further validation with Sanger sequencing for all pathogens. Finally, a comprehensive analysis of epidemiology was performed among different subgroups to investigate the association between infection rates and clinically-relevant information. Results: The sensitivity of STI-HMGS for six target genes was 10 copies/µL. Data derived from the detection of 381 clinical secretions demonstrated that the STI-HMGS exhibited high concordance rate compared with approved commercialized kits and almost 100% sensitivity and specificity for the detection of six sexually transmitted pathogens when validated by Sanger sequencing. Semi-quantitative analysis found that STIs caused by N. gonorrhoeae had a significantly higher (P＜0.05) pathogen load than the other pathogens. Infections caused by C. trachomatis were significantly more common in younger individuals (P＜0.05). We also found that U. urealyticum infections were more likely to happen in females; while the males were more affected by N. gonorrhoeae (P＜0.05). Conclusions: STI-HMGS proved to be an efficient method for the semi-quantitative detection of six important curable STIs pathogens and therefore represents an alternative method for the clinical detection and monitoring of STIs.